FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN PIDIE TAHUN 2010 - 2017 - Lena Marleni; Khairil Anwar (Jurnal Ekonomi Regional Unimal, 2019)
This study aims to analyze the factors that influence the Human Development Index in Pidie Regency in 2010-2017. The data used in this study are secondary data from 2010 to 2017. This model used in this study is the multiple linear regression. The results of the study partially show that the Gross Regional Domestic Product and the Number of labors have a positive and significant effect on the Human Development Index in Pidie Regency from 2010 to 2017. Poverty has a negative and significant effect on the Human Development Index in Pidie Regency from 2010 to 2017. Simultaneously, GDP, poverty and the number of labors have a positive and significant effect on the Human Development Index in Pidie Regency from 2010 to 2017